Psychological Factors in Arabic Writing Skills Al-Insya' Among Year 7 Students in Arabic Schools in Brunei Darussalam: Faktor Psikologi dalam Kemahiran Menulis Bahasa Arab Al-Insya’ di Kalangan Pelajar Tahun 7 di Sekolah Arab Negara Brunei Darussalam - Noorhaizadatul Akmar Metamit; Nur-Ashikin Petra; Shamsinar Husain (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2025)
This study aims to explore and analyze the influence of psychological factors on the mastery of Arabic writing skills, specifically in al-Insya’ (composition) among Year 7 students at an Arabic school in Brunei Darussalam. A mixed-method research approach was employed, incorporating both quantitative and qualitative methods. For the quantitative component, a questionnaire was distributed to 23 students of Year 7 to assess their level of motivation and attitudes toward al-Insya’ writing skills. Meanwhile, the qualitative method involved semi-structured interviews with four Arabic language teachers to gain in-depth insights into the psychological factors affecting students’ performance in al-Insya’ writing.The findings revealed that students’ attitudes toward writing skills were at a moderate level, with intrinsic motivation identified as a more dominant factor than extrinsic motivation in encouraging effective writing. Interviews with teachers further highlighted that factors such as self-confidence, learning environment, and teaching approaches play significant roles in shaping students’ al-Insya’ writing abilities. These findings carry important implications for Arabic language teachers in designing more comprehensive teaching strategies that not only focus on instructional aspects but also consider students’ psychological dimensions. This study also contributes to the growing body of literature in Arabic language education and opens avenues for more in-depth future research. Keywords: Writing Skills, Teaching and Learning, Student Attitudes, Teacher Roles and Motivation.